The 20th Jubilee Colloquium on Regional Sciences: A Conference Report - Viktorie Klímová; Vladimír Žítek; Milan Viturka (Review of Economic Perspectives, 2017)
The history of the International Colloquium on Regional Sciences reaches back to 1998. Over the years, its format has dramatically changed and the Colloquium has become a respected event, which attracts dozens of experts from the field of regional research every year. The contributions focus on the issue of regional disparities, the impact of the public administration activities, the evaluation of the economic, innovation and knowledge potentials of regions, as well as spatial aspects of transport, tourism, population, business environment, and the environment as such. The critical discussions have successfully led to consensus concerning the complex and often long-term problems in the economy of regions. Additionally, the assessment of the impacts of public policies, in particular regional development programmes, is significant. Participants' contributions not only enrich the practice, but many of them considerably extend the theoretical foundations of regional sciences. The Colloquium is also a platform for the creation and development of the links between researchers and academic institutions. All of this represents a significant potential for future years of this event.
Keywords: R11; R12; O12; O18; Z32; 330; region; regional development; competitiveness; innovation; regional disparities; territorial public administration; tourism; rural areas; environment; labour market